Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/jjco/hyw108
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison between proton beam therapy and photon radiation therapy for locally advanced non-small cell lung cancer

Abstract: Objective: To assess the feasibility of proton beam therapy for the patients with locally advanced non-small lung cancer. Methods: The dosimetry was analyzed retrospectively to calculate the doses to organs at risk, such as the lung, heart, esophagus and spinal cord. A dosimetric comparison between proton beam therapy and dummy photon radiotherapy (three-dimensional conformal radiotherapy) plans was performed. Dummy intensity-modulated radiotherapy plans were also generated for the patients for whom curative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…In comparison with photons, PBT plans may deliver lower doses to the adjacent organs at risk, such as the esophagus, lungs and bone marrow, thus improving the therapeutic ratio (15). The early clinical outcome of PBT in lung cancer patients (16)(17)(18)(19)(20)(21)(22)(23) demonstrated that proton beam therapy combined with chemotherapy may relatively reduce the rates of toxicity and achieve a possible survival benefit compared with photon beam therapy and 3DCRT (24). Early results (25)(26)(27)(28)(29) suggested that PBT has the advantage of dose escalation, which may prolong patient survival, lower the risk of recurrence and severe toxicity, and intensify chemotherapy (15).…”
Section: Pbt For Different Cancersmentioning
confidence: 99%
“…In comparison with photons, PBT plans may deliver lower doses to the adjacent organs at risk, such as the esophagus, lungs and bone marrow, thus improving the therapeutic ratio (15). The early clinical outcome of PBT in lung cancer patients (16)(17)(18)(19)(20)(21)(22)(23) demonstrated that proton beam therapy combined with chemotherapy may relatively reduce the rates of toxicity and achieve a possible survival benefit compared with photon beam therapy and 3DCRT (24). Early results (25)(26)(27)(28)(29) suggested that PBT has the advantage of dose escalation, which may prolong patient survival, lower the risk of recurrence and severe toxicity, and intensify chemotherapy (15).…”
Section: Pbt For Different Cancersmentioning
confidence: 99%
“…If the lateral beam placement is avoided to reduce the lung dose, the irradiated dose to heart is consequently increased and results in increased cardiac death in long-term follow-up. In many dosimetric studies, proton therapy demonstrated advantages in lung and heart dose compared with photon therapy [52][53][54]. Several clinical studies have reported treatment outcomes and toxicities of proton therapy in early-stage disease, locally advanced disease, re-irradiation, and in postoperative settings [55].…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%
“…For locally advanced Stage III NSCLC patients, Wu et al. found that proton beam therapy was feasible and superior to three-dimensional conformal radiotherapy for several dosimetric parameters such as the mean dose for lung, heart, and spinal cord [3]. Using IMPT, doses to normal tissues, such as the lung, spinal cord, heart, and esophagus, can be further reduced compared to passive scattering proton therapy and IMRT for extensive Stage IIIB NSCLC, as reported by Zhang et al [10].…”
Section: Dosimetric Advantagesmentioning
confidence: 99%
“…Because of proton beams' finite range, proton beam therapy (PBT) has been increasingly used for lung cancer. Compared to 3D conformal or intensity modulated photon radiation (IMRT), proton beams can better spare the lung, esophagus, heart, cord, and other normal tissues while delivering the same or higher dose to the treatment target [2][3][4]. The dosimetric advantage of proton therapy could lead to potential better tumor control and less toxicity.…”
Section: Introductionmentioning
confidence: 99%